(untitled) - Yourdon, Edward (Upper Saddle River, N.J., 1996)
This book is great. It starts from a description of the case studies and it ends with the implementation. With this book, you can make your first object oriented project a good one with ease! A must have for a beginner on object-oriented projects. I've tried other books, but none compared to this.
Keywords: Lập trình hướng đối tượng (Khoa học máy tính),Object-oriented programming (Computer science)